DINAMIKA DAN REPRODUKSI KEKERASAN PELAJAR DI DENPASAR - Imron Hadi Tamim (Jurusan Sosiologi FISIP UNIB, 2015)
This research aims to explore the students’ violence, its dynamics and the reproduction of violence. As a young person, the student views that the meaning of personal identity is very important for his/her life to be existing in the social world. The “geng pelajar” is the social group which has contributed to students’ personality. This research was held in four senior high schools in Denpasar. The researh used qualitative approach to inquiry the data. The Senior High School students in SMAN Denpasar, SMAN 2 Denpasar, SMAN 3 Denpasar and SMAN 7 Denpasar have many social groups called “geng”. Then the gangs in those schools influenced the member of gangs. The reproduction of violence occurred in the gangs so that the violence was dynamic not static.Keywords: student‘s violence, gangs, dynamic and reproduction